2014
DOI: 10.2527/jas.2014-7811
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postextraction algal residue supplementation on the ruminal microbiome of steers consuming low-quality forage1

Abstract: Cattle consuming low-quality forages (LQF) require protein supplementation to increase forage utilization via ruminal fermentation. Biofuel production from algal biomass results in large quantities of postextraction algal residue (PEAR), which has the potential to elicit LQF utilization responses similar to cottonseed meal (CSM); however, its effect on ruminal bacterial communities is unknown. Five ruminally and duodenally cannulated Angus steers in a 5 × 5 Latin square had ad libitum access to oat straw diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 70 publications
(85 reference statements)
0
18
0
Order By: Relevance
“…Family S24‐7 has been detected in dairy and beef cattle (McCann et al . ; Lima et al . ), however, the role of S24‐7 in the rumen is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family S24‐7 has been detected in dairy and beef cattle (McCann et al . ; Lima et al . ), however, the role of S24‐7 in the rumen is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…We also noted a decrease in family S24-7 as the adaptation steps progressed. Family S24-7 has been detected in dairy and beef cattle (McCann et al 2014;Lima et al 2015), however, the role of S24-7 in the rumen is poorly understood. Bacteria belonging to family S24-7 have been identified in mice fed high fat diets and gluco-oligosaccharides (Serino et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the enrichment of starch degraders, like unclassified S24-7, Prevotella, Bifidobacterium , and Ruminobacter , may be due to greater starch availability in the colon during starter feeding. Other studies have demonstrated the presence of family S24-7 in dairy and beef cattle (McCann et al, 2014; Lima et al, 2015; Anderson et al, 2016); however, the role of S24-7 in the colon of ruminants remains poorly understood. Bacteria belonging to family S24-7 have also been identified in the colons of mice fed high-fat diets and gluco-oligosaccharides (Serino et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These results could be related to impacts on rumen microflora. McCann et al [36] examined the effects of Chlorella spp. LEB on the ruminal microbiome.…”
Section: Ruminant Animalsmentioning
confidence: 99%